Environmental security and its implications for China's foreign relations - Junko Mochizuki; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2011)
China's emerging standing in the world demands a major rethinking of its diplomatic strategies. Given its population size, geographical scale, economic power and military presence, China is poised to play a larger political role in the twenty-first century, and is thus perceived by the international community to have greater capacities, capabilities and responsibilities. At the same time, environmental stresses caused by China's energy and resources demands have become increasingly evident in recent years, urging China to cultivate delicate diplomatic relations with its neighbors and strategic partners. Tensions have been seen in areas such as transboundary air pollution, cross-border water resources management and resources exploitation, and more recently in global issues such as climate change. As the Chinese leadership begins to embrace the identity of a responsible developing country, it is becoming apparent that while unabated resources demands and environmental deterioration may pose a great threat to environmental security, a shared sense of urgency could foster enhanced cooperation. For China to move beyond existing and probable diplomatic tensions, a greater attention to domestic and regional environmental security will no doubt be necessary. This article explores such interrelations among domestic, regional and global environmental securities and China's diplomacy, and suggests possible means by which China could contribute to strengthening global environmental security.
Keywords: Q25; Q34; Q48; Q42; Q53; Q54; Q56; Q58; O13; P28; 330; Acid Rain; Climate Change; Energy; Environmental Security; Transboundary Air Pollution; Water Resource Management; Asia